Vitis vinifera Turkish novel table grape 'Karaerik'. Part II: Non‐anthocyanin phenolic composition and antioxidant capacity. (19th July 2021) - Pérez‐Navarro, José; Hermosín‐Gutiérrez, Isidro; Gómez‐Alonso, Sergio; Kurt‐Celebi, Aynur; Colak, Nesrin; Akpınar, Erdal; Hayirlioglu‐Ayaz, Sema; Ayaz, Faik A
Abstract: BACKGROUND: 'Karaerik' is a novel table grape ( Vitis vinifera L.) native to Turkey and widely cultivated in areas bordering the city of Erzincan. Because of the demonstrated beneficial effects on human health of the grape phenolic composition, the aim of this work was to conduct a detailed profiling of non‐anthocyanin phenolic fractions from different grape tissues of the 'Karaerik' table grape. Both qualitative and quantitative characterization of phenolic compounds were achieved using high‐performance liquid chromatography–diode array detection–electrospray ionization–tandem mass spectrometry. Total phenolic content and oxygen radical absorbance capacity were also determined to evaluate the antioxidant properties of this table grape. RESULTS: A high number of non‐anthocyanin phenolic compounds was identified in 'Karaerik' table grape skins and seeds, including 11 flavonols, six hydroxycinnamic acid derivatives, two stilbenes, several monomeric and dimeric flavan‐3‐ols and proanthocyanidins. Quercetin‐type derivatives dominated the flavonol profile of grape skins, followed by myricetin type. Tartaric acid esters of three acids (caffeic, coumaric and ferulic acids) were the main hydroxycinnamic acid derivatives in this cultivar. Qualitative and quantitative differences were observed in flavan‐3‐ol composition among the grape tissues. Proanthocyanidins were the most abundant class of phenolic compounds in 'Karaerik' grapes, being mainly located in seeds. Higher antioxidant capacity values were determined in grape seeds, in correlation with the total phenolic content. CONCLUSION: These results provide useful information for a better understanding of phenolic antioxidants from the 'Karaerik' table grape and will contribute to promoting the varietal identity and health‐related properties of this fruit. © 2021 Society of Chemical Industry.